Analysis of the Reception of Sexual Violence in Like & Share Films - Budiman, Arif Imam; Wibowo, Arif Ardy (MEDIASI Jurnal Kajian dan Terapan Media, Bahasa, Komunikasi, 2024)
Sexual violence is a very troubling phenomenon in society because it can cause physical, sexual, and psychological suffering for victims. In Indonesia, several films have raised the theme of sexual violence inspired by true stories, one of which is a teen drama film entitled Like & Share. This study aims to understand how the audience interprets and responds to sexual violence in the movie. The method used is descriptive semi-structured qualitative research with Stuart Hall's reception analysis. Data were collected through interviews and documentation from ten informants aged 18-24, who were classified into three reception categories: dominant hegemonic position, negotiated position, and oppositional position. The results showed that five informants were in the dominant hegemonic position category, which means they agreed with the movie's message regarding sexual violence. Three informants were in the negotiated position category, indicating they agreed but added personal views. Two informants were in the oppositional position category, showing their disagreement with the movie's message.